2005
DOI: 10.1073/pnas.0509693102
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate microarray for profiling the antibodies interacting with Globo H tumor antigen

Abstract: Understanding the specificity of cell-surface carbohydrates interaction with antibodies and receptors is important for the development of new therapeutics and high-sensitivity diagnostics. This approach is, however, limited to the availability of natural and truncated sequences of the oligosaccharides and the sensitivity of the assay system. Reported here is the synthesis of the cancer antigen Globo H hexasaccharide, an epitope found on the cell surface of breast, prostate, and ovarian cancers, and its truncat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
150
0
2

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 187 publications
(157 citation statements)
references
References 50 publications
5
150
0
2
Order By: Relevance
“…GH A was synthesized by a new programmable one-pot strategy developed by our laboratory (19) and reacted with a p-nitrophenyl ester homobifunctional linker (39,40) to yield the half ester B, which after purification, was incubated with a carrier protein as shown in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…GH A was synthesized by a new programmable one-pot strategy developed by our laboratory (19) and reacted with a p-nitrophenyl ester homobifunctional linker (39,40) to yield the half ester B, which after purification, was incubated with a carrier protein as shown in Scheme 1.…”
Section: Resultsmentioning
confidence: 99%
“…GH is also expressed weakly in normal tissue but only restricted to apical epithelial cells at lumen borders, a site that seems to be immune-inaccessible (9,(15)(16)(17). Moreover, higher levels of anti-GH Ab were detected in the plasma of breast cancer patients (18)(19)(20). Our previous study also revealed that the expression of some glycans, such as GH and Stage-specific embryonic antigen 3 (SSEA3) (also called Gb5), was observed on breast cancer cells and breast cancer stem cells (BCSCs) (21).…”
mentioning
confidence: 89%
“…Thus, the microarray may provide a more appropriate and more sensitive system for studying protein-carbohydrate interactions than the traditional solution-phase ELISA analysis. Recently, our group has used Globo H and its truncated analog microarrays to profile the binding specificity of its monoclonal and polyclonal antibodies in a qualitative manner (38). In that preliminary study, we found that the polyclonal antibodies from a breast cancer patient can bind both Globo H and its truncated analog without fucose (Gb5), whereas Mbr1 is specific for Globo H (38).…”
mentioning
confidence: 97%
“…Recently, our group has used Globo H and its truncated analog microarrays to profile the binding specificity of its monoclonal and polyclonal antibodies in a qualitative manner (38). In that preliminary study, we found that the polyclonal antibodies from a breast cancer patient can bind both Globo H and its truncated analog without fucose (Gb5), whereas Mbr1 is specific for Globo H (38). The binding specificity studies of monoclonal antibodies and human polyclonal antibodies associated with Globo H have prompted us to further investigate the following questions: (i) Are Globo H and Gb5 differentially expressed in disease stages?…”
mentioning
confidence: 99%
“…Such natural antibodies may play important roles in host defense against microbial invasion and/or in immunoregulation. Amongst the well-studied anti-glycan natural antibodies in humans are the anti-blood group antibodies (Pal et al, 2004;Dinglasan et al, 2005) and antiGal-α-1,3-Gal antibodies (Galili, 2005;Huang et al, 2006). Other known anti-carbohydrate human natural antibodies include those specific for Gal-β-1,3-GalNac (T antigen) and lactose (Gupta et al, 1996;Galili, 2001).…”
Section: Introductionmentioning
confidence: 99%